The Circassian Genocide - Richmond, Walter (Genocide, Political Violence, Human Rights, 2013)
Circassia was a small independent nation on the northeastern shore of the Black Sea. For no reason other than ethnic hatred, over the course of hundreds of raids the Russians drove the Circassians from their homeland and deported them to the Ottoman Empire. At least 600,000 people lost their lives to massacre, starvation, and the elements while hundreds of thousands more were forced to leave their homeland. By 1864, three-fourths of the population was annihilated, and the Circassians had become one of the first stateless peoples in modern history. Using rare archival materials, Walter Richmond chronicles the history of the war, describes in detail the final genocidal campaign, and follows the Circassians in diaspora through five generations as they struggle to survive and return home. He places the periods of acute genocide, 1821–1822 and 1863–1864, in the larger context of centuries of tension between the two nations and updates the story to the present day as the Circassian community works to gain international recognition of the genocide as the region prepares for the 2014 Winter Olympics in Sochi, the site of the Russians’ final victory